2006
DOI: 10.1177/070674370605100809
|View full text |Cite
|
Sign up to set email alerts
|

Oxcarbazepine in the Treatment of Bipolar Disorder: A Review

Abstract: A lthough lithium is considered the gold standard of treatment for BD, research and clinical experience over the past 4 decades have indicated that only a small proportion of patients with BD remain episode-or symptom-free using lithium monotherapy in long-term maintenance treatment (1,2). Thus, to improve outcomes for a substantial number of patients with BD, anticonvulsants and atypical antipsychotics are often used as alternatives or augmentation strategies to lithium. Among anticonvulsants, VPA and CBZ hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…The usual daily doses range from 300 to 2700 mg for the treatment of seizures [251] and 600-2400 for BD [252].…”
Section: Oxcarbazepinementioning
confidence: 99%
“…The usual daily doses range from 300 to 2700 mg for the treatment of seizures [251] and 600-2400 for BD [252].…”
Section: Oxcarbazepinementioning
confidence: 99%
“…In general, OXC is well tolerated [41]. The incidence of adverse effects during OXC therapy was similar to placebo (90 vs 79%) [10,26].…”
Section: Safety and Tolerabilitymentioning
confidence: 80%
“…Hyponatremia has been associated with the use of OXC, more frequently than CBZ. It is more likely to occur in older patients and patients using diuretics (it is rare in children) [41]. The reported incidence ranges from 0 to 31%.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Although oxcarbazepine does not have the FDA indication for the treatment of bipolar disorder, a recent review reported efficacy in acute mania and that it may be a useful add‐on in treating bipolar depression and bipolar maintenance (Pratoomsri, Yatham, Bond, Lam, & Sohn, 2006). Also, the TIMA (Suppes et al., 2005) guidelines for bipolar mania/hypomania list oxcarbazepine in Stage 3 of the treatment algorithm.…”
Section: Treatmentmentioning
confidence: 99%